Is Multifactorial Sex Determination in the House Fly, Musca domestica (L.), Stable Over Time?. (18th August 2016) - Meisel, Richard P.; Davey, Taira; Son, Jae Hak; Gerry, Alec C.; Shono, Toshio; Scott, Jeffrey G.
Abstract: Sex determination pathways evolve rapidly, usually because of turnover of master regulatory genes at the top of the developmental pathway. Polygenic sex determination is expected to be a transient state between ancestral and derived conditions. However, polygenic sex determination has been observed in numerous animal species, including the house fly, Musca domestica . House fly males carry a male-determining factor (M) that can be located on any chromosome, and an individual male may have multiple M factors. Females lack M and/or have a dominant allele of the Md-tra gene ( Md-tra D ) that acts as a female-determining locus even in the presence of multiple copies of M. We found the frequency and linkage of M in house flies collected in Chino, CA (USA) was relatively unchanged between 1982 and 2014. The frequency of females with Md-tra D in the 2014 collection was 33.6% ( n = 140). Analysis of these results, plus previously published data, revealed a strong correlation between the frequencies of Md-tra D and multiple M males, and we find that these populations are expected to have balanced sex ratios. We also find that fitness values that allow for the invasion and maintenance of multiple sex determining loci suggest that sexually antagonistic selection could be responsible for maintaining polygenic sex determination in house fly populations. The stability over time and equilibrium frequencies within populations suggest the house fly polygenic sex determination system is not in transition, and provide guidance for future investigations on the factors responsible for the polymorphism.